2022
DOI: 10.31635/ccschem.021.202100945
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen Functionalization Affording Structurally Well-Defined Cobalt Diazenido Complexes

Abstract: Cobalt-bis(dinitrogen) complexes [LCo(N 2 ) 2 ] − (3,4) with simple and commercially available bidentate phosphine ligands (L: Cy 2 PCH 2 CH 2 PCy 2 ) were synthesized and structurally characterized. Further N 2 functionalization by treating the complex 3b with i Pr 3 SiCl afforded the first structurally characterized cobalt diazenido complex 5. These complexes 3-5 were found to be effective catalysts for the transformation of N 2 into N(SiMe 3 ) 3 . The electronic structure of the cobalt diazenido complex 5 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The product was identified to be a silylated S8). More importantly, its spectroscopic features 45,46 3i and S80), and significant red shifts 48 of ν N−N by at least 200 cm −1 in the IR spectra (Figures S18−S26). TD-DFT calculations predicted that the low-lying excitation of 3-Me appears at 608 nm, which matches the experiment (630 nm) very well (Figure 3a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The product was identified to be a silylated S8). More importantly, its spectroscopic features 45,46 3i and S80), and significant red shifts 48 of ν N−N by at least 200 cm −1 in the IR spectra (Figures S18−S26). TD-DFT calculations predicted that the low-lying excitation of 3-Me appears at 608 nm, which matches the experiment (630 nm) very well (Figure 3a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Following this route of reasoning, [Cp*­(depe)­Cr II –NN–Si i Pr 3 ] ( 3-Si i Pr 3 ) bearing a more bulky Si i Pr 3 substituent could be independently accessed with an isolated yield of 88% by a combination of 1 with i Pr 3 SiCl at 193 K. Single-crystal X-ray crystallography analyses demonstrated that the molecular structure of 3-Si i Pr 3 features a lengthened N–N (1.224(2) Å) and a shortened Cr–N α (1.7061(15) Å) bond (Figure ) relative to those measured for 1-crypt (N–N: 1.156(3) and 1.160(3) Å; Cr–N α : 1.7955(19) and 1.788(2) Å) (Table S8). More importantly, its spectroscopic features , (δ­( 15 N) = 390.83 and 222.07 ppm; ν N–N = 1611 cm –1 , ν N–N = 1553 cm –1 for 15 N-labeled 3-Si i Pr 3 - 15 N 2 ) (Figures h, S11, and S12) closely resemble those of 3-Me and 3-SiMe 3 , which supports our assignments of 3-Me and 3-SiMe 3 as diazenido species.…”
Section: Resultsmentioning
confidence: 99%
“…555 Nitrogen functionalization has been achieved at cobalt complexes with chelating phosphine ligands. 556,557 In 2019, Miller and Long described Co(−I)-dinitrogen complexes featuring two examples of the triphos family of tripodal ligands, specifically N-triphos and C-triphos. 556 547,548,558 848 and 849 coordinate dinitrogen between the cobalt centers and the stabilizing Mg 2+ cation in an end-on bridging fashion.…”
Section: General Comments On N 2 Activation By Metalate Complexes The...mentioning
confidence: 99%
“…[ 10‐13 ] Hence, a variety of strategies have been developed to achieve dinitrogen reduction more efficiently and in an environmentally‐friendly manner. [ 14‐37 ]…”
Section: Introductionmentioning
confidence: 99%